2021
DOI: 10.3389/fcvm.2021.583320
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte to High-Density Lipoprotein Ratio but Not Platelet to Lymphocyte Ratio Effectively Predicts Metabolic Syndrome Among Subjects From Rural China

Abstract: Background: This study intended to use two novel inflammatory indicators: lymphocyte to high-density lipoprotein cholesterol ratio (LHR) and platelet to lymphocyte ratio (PLR), to predict newly diagnosed metabolic syndrome (MetS) among subjects from rural Northeast China.Methods: Adult participants without MetS at baseline (n = 4,980, age = 52.65 ± 10.21 years; 51.9% men) were originated from the Northeast China Rural Cardiovascular Health Study (NCRCHS). LHR (Q1: ≤1.04; Q2: 1.04–1.35; Q3: 1.35–1.79; Q4: ≥1.79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…LHR was proposed by Chen et al 12 as a novel inflammatory indicator. Consistent with the results from Chen et al ,12 other studies have confirmed the role of LHR in predicting the presence and severity of metabolic syndrome 20 21. Considering the close relationship between metabolic syndrome and atherosclerosis, it is reasonable to wonder on the effect of LHR on the development of CAD.…”
Section: Introductionsupporting
confidence: 80%
“…LHR was proposed by Chen et al 12 as a novel inflammatory indicator. Consistent with the results from Chen et al ,12 other studies have confirmed the role of LHR in predicting the presence and severity of metabolic syndrome 20 21. Considering the close relationship between metabolic syndrome and atherosclerosis, it is reasonable to wonder on the effect of LHR on the development of CAD.…”
Section: Introductionsupporting
confidence: 80%
“…Obtaining the numbers of neutrophils, monocytes, lymphocytes, and platelets is inexpensive and easy via complete blood count, which are altered when an organism is inflamed. Furthermore, new hematological parameters related to HDL-C and complete blood cells, such as NHR ( 8 ), MHR ( 9 ), LHR ( 10 ), PHR ( 11 ), SII ( 12 ), SIRI ( 13 , 14 ), and AISI ( 15 ) have been proposed as novel inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…LHR could act as an index of inflammatory status according to previous studies (H. Chen et al, 2019;T. Chen et al, 2020;Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…LHR: lymphocyte to high-density lipoprotein ratio; BMI: body mass index. 2020) that can predict the occurrence and severity of MetS (Yu et al, 2021). Cytokines and proteolytic enzymes induced by chronic inflammation, insulin, and insulin growth factors, I and II may explain the association between LHR and MetS (Lao et al, 2008;Pasini et al, 2010;Tamariz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%